Studi Literatur: Wordwall sebagai Media Pembelajaran dalam Meningkatkan Motivasi dan Hasil Belajar Matematika Siswa Sekolah Dasar - Rahmawati, Sisca; Amri, Mira Amelia; Putra, Adi (Papanda, 2025)
This study aims to thoroughly analyze the impact of Wordwall as a learning tool on increasing motivation and learning outcomes in mathematics among elementary school students. The method used was a literature review with a qualitative approach. Data were obtained from ten articles published in the past five years with a focus on Wordwall criteria, motivation and learning outcomes for mathematics at the elementary school level. Based on the results of the study, the use of wordwalls was proven to increase focus, interest, self-confidence and learning satisfaction. Word walls also support active and fun learning, making it easier for students to understand math concepts. Their implementation has been shown to significantly increase learning motivation and learning satisfaction at various levels. However, there are several obstacles to its implementation, including the need for devices, the Internet and teachers' skills in developing word wall features. It is expected that this study will provide a reference for teachers to use Wordwall optimally and encourage further research on digital learning media in elementary schools.